2012
DOI: 10.1111/j.1750-8606.2012.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Children and Youth in Military Families: Toward Developmental Understandings

Abstract: Nearly, 2 million children in the United States live in military families. Throughout all branches of the U.S. military since September 11, 2001, ca 700,000 children have had or currently have a parent deployed to the combat zones of Iraq or Afghanistan. As a result, researchers are paying increasing attention to the effects of military deployment on children and families. These facts and the changing landscape of military service point to the need to empirically examine the impact of parental military deploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…Research has indicated that maternal mental health can mitigate the impact of OSI on child development (Dinshtein, Dekel, & Polliack, 2011;Lambert, Holzer, & Hasbun, 2014;Lieberman & Horn, 2013;Lincoln & Sweeten, 2011;Maholmes, 2012;McGuinness & McGuinness, 2014). A study that examined the impact of warm and caring maternal relationships on the children of PTSD veterans indicated that, as adults, children of PTSD veterans experienced less emotional distress and had a greater capacity for intimacy (Dinshtein et al, 2011).…”
Section: Spousal Relationships and Parentingmentioning
confidence: 96%
“…Research has indicated that maternal mental health can mitigate the impact of OSI on child development (Dinshtein, Dekel, & Polliack, 2011;Lambert, Holzer, & Hasbun, 2014;Lieberman & Horn, 2013;Lincoln & Sweeten, 2011;Maholmes, 2012;McGuinness & McGuinness, 2014). A study that examined the impact of warm and caring maternal relationships on the children of PTSD veterans indicated that, as adults, children of PTSD veterans experienced less emotional distress and had a greater capacity for intimacy (Dinshtein et al, 2011).…”
Section: Spousal Relationships and Parentingmentioning
confidence: 96%
“…A growing number of families have experienced the strain of wartime deployments and reintegration over the past decade (Adler et al 2011;Maholmes 2012; Office of the Deputy Under Secretary of Defense for Military Community andFamily Policy 2009, 2010;Saltzman et al 2011). The deployment cycle (pre-deployment, deployment, postdeployment or reintegration) challenges families with its multiple and lengthy separations and has been linked to stress for family members.…”
Section: Introductionmentioning
confidence: 98%
“…Since the start of OEF/OIF/OND, more than two million children of U.S. service members have been affected by wartime deployments (Esposito-Smythers et al, 2011). For more than a decade since 9/11, children and their parents have negotiated repeated separations and subsequent family reunions in the context of wartime stress and the related imminent risk factors (Maholmes, 2012). An entire generation has grown up in the context of war, yet a great divide exists between military-connected children, who have S132 (2013) sustained repeated losses and reintegration stress, and their civilian peers, who have lived without these risk factors present in their lives.…”
Section: Curricula Inclusionmentioning
confidence: 98%
“…For instance, social workers need to be familiar with research methods that are culturally-competent and support research efforts on the different effects of the deployment cycle, particularly the reintegration phase that can affect a family system for years with implications for all members. There are more than two million American military-connected children who have grown up during more than a decade of war, and there is currently very little research about the long-term effects on their well-being and psychosocial development (Maholmes, 2012). The high number of veterans with polytrauma (multiple injuries to various body systems) as well as PTSD and TBI from Iraq and Afghanistan MILITARY/VETERAN ISSUES IN SOCIAL WORK EDUCATION S139 are a cohort that would benefit from continued research into treatments that prove effective over time.…”
Section: S135mentioning
confidence: 99%